2015
DOI: 10.1161/strokeaha.114.006782
|View full text |Cite
|
Sign up to set email alerts
|

Diffusional Kurtosis and Diffusion Tensor Imaging Reveal Different Time-Sensitive Stroke-Induced Microstructural Changes

Abstract: Background and Purpose Diffusion magnetic resonance imaging (dMRI) is a promising, clinically feasible imaging technique commonly used to describe white matter changes following stroke. We investigated the sensitivity of dMRI to detect microstructural alterations in grey matter following sensorimotor cortex (SMC) stroke in adult male rats. Methods The mean diffusivity (MD) and mean kurtosis (MK) of peri-lesion motor cortex (MC) was compared to measures in the contra-lesional forelimb area of SMC at 2h, 24h, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 28 publications
7
66
3
Order By: Relevance
“…Aside from yielding all of the diffusion indices conventionally obtained with diffusion tensor imaging (DTI), DKI also gives metrics of non-Gaussian diffusional, such as mean (MK), axial (K // ) and radial (K ⏊ ) kurtoses, which more comprehensively characterize brain cytoarchitecture. Our own animal investigations, as well as studies from other groups, have shown that DK metrics are sensitive to changes in brain microstructural complexity that may be associated with brain development [93], Aβ deposition [94], stroke [95, 96], and myelin abnormalities [97]. …”
Section: Neuroimaging Of Mouse Models Of Down Syndromementioning
confidence: 99%
“…Aside from yielding all of the diffusion indices conventionally obtained with diffusion tensor imaging (DTI), DKI also gives metrics of non-Gaussian diffusional, such as mean (MK), axial (K // ) and radial (K ⏊ ) kurtoses, which more comprehensively characterize brain cytoarchitecture. Our own animal investigations, as well as studies from other groups, have shown that DK metrics are sensitive to changes in brain microstructural complexity that may be associated with brain development [93], Aβ deposition [94], stroke [95, 96], and myelin abnormalities [97]. …”
Section: Neuroimaging Of Mouse Models Of Down Syndromementioning
confidence: 99%
“…Diffusional kurtosis has been investigated to explore tissue reversibility in acute cerebral infarction. [14][15][16] However, there is a paucity of information regarding the microstructural properties measured by DKI in chronic ischemia in living humans. To expand on our prior DTI study, we investigated whether adults with MMD and no overt cerebral infarctions have altered diffusional kurtosis in the entire cerebrum.…”
mentioning
confidence: 99%
“…Despite its sensitivity, DKI is microstructurally unspecific, causing studies with comparison of DKI metrics to histology to be needed to understand how disease related microstructural alterations are reflected in DKI (regardless of metric definitions and acquisition methods). Such studies have been carried out for experimental stroke [5,90], stress and depression [60,91], and kidney fibrosis [62] to name a few. Furthermore, studies have been performed to elucidate the relation between DKI metrics and tissue magnetic susceptibility [92,93] with results suggesting a susceptibility contribution in DKI metrics warranting further investigation.…”
Section: Future Directions For the Fast Kurtosis Techniquesmentioning
confidence: 99%
“…Several of these DKI metrics have been shown to detect subtle changes in brain tissue structure. To briefly summarize, studies have shown DKI to have potential in diagnostics of a number of diseases such as stroke [4,5], Alzheimer's disease [6], multiple sclerosis [7], gliomas [8,9], and head trauma [10][11][12] (see also the review of this area in Ostergaard et al [13]). DKI is not only of clinical interest but is also a valuable tool in basic neuroscience, and the method has for example been employed in studies of natural alteration of brain microstructure e.g., in the context of development and aging [14,15].…”
Section: Introductionmentioning
confidence: 99%